Signal coverage mapping of local radios (Journal on Geoinformatics, Nepal, 2017)
FM radio transmission is greatly affected by geography. Nepal faces particular problems in relation to variations in signal reach because of its varying topography. Radio signal coverage mapping indicates service areas of radio communication transmitting stations. The objectives of this study are to map the signal coverage of local radios (Kavre district) and to assess parameters affecting FM signal strength. The primary data were GPS coordinates of FM transmission stations and bearing of antenna. The secondary data regarding frequency of station, transmitter model, transmitter power, antenna model, and height of antenna from ground level were collected from respective FM stations. For elevation data freely available SRTMv3 was used. Combined Cartesian coverage maps for each FM stations were prepared using Radio Mobile software that showed varying signal strength of station in dBμV/m. The accuracy of the maps through field validation was observed to be 85%. Assessment of parameters affecting FM signal strength concluded that increase in antenna elevation, gain of antenna and power of transmitter increases the signal coverage.